2005
DOI: 10.1093/eurpub/cki033
|View full text |Cite
|
Sign up to set email alerts
|

Pain in primary care: an Italian survey

Abstract: The study identified a high proportion of contacts with pain in Italian general practice, with widespread use of drugs. The distribution of chronic and acute pain was rather similar and musculoskeletal pain was the most frequent form. Most types of prescriptions were closely related to certainty of diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 21 publications
3
36
2
10
Order By: Relevance
“…These results do not differ significantly from other European practice studies [14][15][16]. Our practice study found the highest prevalence of chronic pain in the 70-79-year-old age group.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…These results do not differ significantly from other European practice studies [14][15][16]. Our practice study found the highest prevalence of chronic pain in the 70-79-year-old age group.…”
Section: Discussioncontrasting
confidence: 60%
“…Studies carried out in primary care settings in Finland [13], Sweden [14], Denmark [15], and Italy [16] showed point prevalence rates of 15-20%. Two small, nonrepresentative studies (one practice, respectively) were carried out in German general practice and demonstrated two different chronic pain ratios: 35% [17] and 20% [18].…”
Section: Introductionmentioning
confidence: 99%
“…La incidencia y prevalencia del dolor neuropático exacta se desconoce. Las estimaciones de prevalencia que se basan en causas específicas de dolor neuropático tienden a ser más bajas (2,1 %) que las fundamentadas en informes de los síntomas clásicos, proporcionando éstas valores de 6-8 %; en España se cifra en un 7,7 %, incluso más alta según distintos estudios (3). En cualquier caso, una mejor estimación de prevalencia poblacional del dolor con características neuropáticas es probable que se sitúe entre el 6,9 y el 10 % (4).…”
Section: Introductionunclassified
“…Most are national or regional studies [BASSOLS & AL., 1999;ELLIOTT & AL., 1999;KOLEVA & AL., 2005, LANTERI-MINET & AL., 2003, or compilations of national studies [GOUDAS & AL., 2005]. However, these studies only focused on specific pain disability (e.g.…”
Section: Introductionmentioning
confidence: 99%